Employee Development in Bank Sector based on Potential Review Assessment with 9 Box Model Talent Management - Purbasari, Rafika Nirmala; Syarifah, Dewi (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
This research about potential review assessment is carried out to provide an overview of the competencies possessed by Bank X employees. Potential review is known to provide competency profiles and become the basis of employee development strategies. This assessment is a part of talent management. The existence of the right talent management system within organization can increase employee retention. Researcher has been able to get the information of employee’s KPI score and gave psychological assessment, to be able to do the employee mapping. The two dimensions, potential competencies and KPI score are known to be the basis in determining the nine-box model. The subject in this research is a junior staff financial institution in Bank X. Based on the assessment that has been carried out, she is included in “rising star” category, because he has “moderate” work performance and “high” potential competency profile. The result of this assessment will be used by organization as talent pooling information.Asesmen potential review ini dilakukan untuk memberikan gambaran kompetensi yang dimiliki oleh karyawan Bank X. Potential review diketahui dapat memberikan profil kompetensi karyawan dan menjadi dasar strategi pengembangan karyawan. Adanya penilaian potensi kompetensi pada karyawan dapat membantunya bersiap untuk melakukan pengembangan diri. Asesmen ini termasuk dalam bagian talent management. Adanya pengelolaan talenta yang tepat di dalam organisasi dapat meningkatkan retensi karyawan. Selain memberikan pengukuran psikologis untuk dapat memetakan profil karyawan, organisasi juga perlu memperhatikan penilaian kinerja. Kedua dimensi tersebut, potensi kompetensi serta performansi kerja karyawan secara riil adalah dasar dalam menentukan posisi karyawan melalui model nine-box. Subjek penelitian ini menduduki jabatan junior staff financial institution. Berdasarkan asesmen yang telah dijalankan, ia termasuk ke dalam kategori “rising star”, karena berada pada performansi kerja “moderate” dan profil potensi kompetensi “high”. Hasil asesmen ini akan digunakan organisasi sebagai dasar talent pooling.